Diversifikasi Distribusi UMKM Sapu-Keset Desa Slahung melalui Pengabdian Masyarakat untuk Kemandirian Ekonomi - Tonny Ilham Prayogo; Muhammad Fauzy Rahmanto; Bramantio Drajat Abdi Nugroho; Muhammad Soni Amrulloh (LP3M IAIFA Kediri, 2026)
Micro, Small, and Medium Enterprises (UMKM) play a crucial role in supporting the rural economy, yet many UMKM actors still face limitations in product marketing and promotion. This condition is also experienced by the broom and woven mat handicraft business owned by Mr. Suparman in Desa Persiapan Argo Mulyo, Slahung Sub-district, Ponorogo Regency. This study aims to describe the mentoring activities conducted to enhance the visibility of the partner's business. A qualitative descriptive approach was employed through: (1) participatory observation of catalog creation and WhatsApp Business implementation; (2) interviews with 1 partner and 20 customers (80% positive response, 30 new contacts); (3) documentation of before-and-after photos and visit monitoring (+25%). The focus was on evaluating partner readiness for 4 distribution diversification strategies for UMKM broom-mat businesses in Slahung Village. The results show that creating promotional banners, compiling product descriptions, and using WhatsApp Business improved the business's professional appearance and facilitated consumer communication. This activity successfully strengthened partner business promotion through realized interventions, providing significant initial contributions to the economic independence of UMKM broom-mat businesses in Slahung Village.